STRATEGI USAHA KECIL MENENGAH PENJUAL SEMBAKO DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT DESA PEMANGKET KECAMATAN KURIPAN UTARA KABUPATEN LOMBOK BARAT - Intania Fandana; Dewi Rispawati (Bajang Institute, 2023)
This research is themed Strategy of Small and Medium Enterprises of Grocery Sellers in Improving the Welfare of the Community of Pemangket Village, North Kuripan District, West Lombok Regency. The aims of this study were (1) to find out how the prospects for small and medium businesses selling basic necessities in Pemangket Village, North Kuripan District, West Lombok Regency, and (2) to find out how the strategies of small and medium businesses selling basic necessities in Pemangket Village, North Kuripan District, West Lombok Regency in improving public welfare. This research method uses a qualitative approach to data collection techniques through observation, interviews (interviews) and documentation. Based on the results of the study, (1) the prospects for small and medium businesses selling basic necessities play an active role in improving the welfare of the community, namely where the average community as the owner of a basic food stall business says that this business is able to provide more income than doing this business, even though the level of welfare is only part business owners who have just reached this level in the sense of business owners who have been doing this business for a long time. (2) The strategy for developing a basic food seller business in improving people's welfare, namely (a) processing the products owned, (b) conducting consistent promotions or advertisements, (c) providing affordable and competitive prices, and providing maximum service to consumers or customers, (d) establishing harmonious relationships with internal and external parties of the company. (e) Try hard, earnest and willing to learn.